PRT4165 nanocomposite promoting epigenetic retardation through proteasomal depletion of polycomb in acute myeloid leukemia. (December 2020) - Kushwaha, Avinash Chandra; Kaundal, Babita; Dev, Atul; Srivastava, Anup Kumar; Mohanbhai, Soni Jignesh; Karmakar, Surajit; Choudhury, Subhasree Roy
Highlights: Encapsulation of PRT4165 in human serum albumin circumvents its therapeutic limitations such as poor aqueous solubility and physiological instability. PRT4165 nanocomposite enhances the apoptosis pathway in vitro and in vivo acute myeloid leukemia (AML) model compared to bare PRT4165. PRT4165 nanocomposite halts the epigenetic pathway through the degradation of polycomb protein, Bmi1 via ubiquitin proteasome pathway. A transcription factor, C-Myb directly regulates the Bmi1 activity in vitro and in vivo AML models. Abstract: The polycomb repressive complex 1 (PRC1) protein, Bmi1 is overexpressed in acute myeloid leukemia and mediates histone H2A monoubiquitination through its ubiquitin (E3) ligase activity. The 2-pyridine-3-yl-methylene-indan-1, 3-dione (PRT4165) inhibits PRC1-mediated H2A monoubiquitination but the poor aqueous solubility, and physiological instability limit its application. In current study, the encapsulation of PRT4165 in human serum albumin nanoparticles (HSANPs) improved its therapeutic efficacy as evident through the enhanced apoptosis, sub-G1 cell cycle arrest, depolarized mitochondrial membrane, reactive oxygen species generation and caspase 3 activation. The nanoformulation repressed Bmi1 through ubiquitin-proteasome pathway (UPP) and regulated H2AK119 ubiquitination in AML cells. Co-immunoprecipitation studies revealed the direct interaction of Bmi1 and C-Myb, a crucial regulator of AML pathogenesis. Moreover, PRT4165 encapsulated HSANPs showed improved in vivo biodistribution, better dispersibility and biocompatibility, and exhibited enhanced suppression of leukemia stem cell marker, CD45 + and activation of myeloid monocytes differentiation marker, CD11b + in AML xenograft mouse model. Graphical abstract: Schematic represents the mechanism of PRT4165 loaded HSANPs mediated enhanced AML therapy through the deactivation of Bmi1 by the ubiquitin-proteasome pathway (UPP). Image, graphical abstract